The Feynman lectures on physics - Leighton, Robert B. (Pearson, 2011)
This revised edition of Feynman's legendary lectures includes extensive corrections Feynman and his colleagues received and Caltech approved, making this the definitive edition of The Feynman Lectures on Physics. For all readers interested in physics.